Strategi Promosi Pengelola Kawasan Wisata Rammang-rammang Maros dalam Meningkatkan Kunjungan Wisatawan setelah Pandemi Covid - Anaam Maruf; Nahdiana Nahdiana (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2024)
This research aims to describe what are the promotional strategy of the manager of the Rammang-rammang tourism site post Covid-19, in which Rammang-rammang is the second largest karst area in the world and has extraordinary tourism potential. This research also wants to reveal the supporting and inhibiting factors in the implementation of the strategy. This type of research is descriptive research with a qualitative approach. Data were collected using interviews and observation methods. The results showed that the promotional strategy of the manager of the Rammang-rammang tourist area in increasing tourist visits after the Covid -9 pandemic was Word of Mouth, promotion through the use of social media, panoramic documentary videos of the Rammang-rammang tourist area. Some of the things that support the implementation are adequate road infrastructure, awareness, and partnerships. Other factors include supporting technomateriality. While the inhibiting factors are accommodation infrastructure, facilities, and services. In addition, field findings show that there is an internal conflict factor in the management which is an obstacle to the implementation of marketing strategies.